Bersama Membangun Gapura Desa: Gotong Royong Mewujudkan Ikon Baru Desa Kota Guring, Kec.Rajabasa, Kab.Lampung Selatan - Kanada Komariyah; Caca Ramanda; Oktia Tri Komala; Robi Zulfikar; Aisyah Wahyuni; Mea Puspita Sari; Erna finayunita; Khoirul Riyansyah; Rayendra Valoga (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2024)
Kota Guring Village is located in Rajabasa District and has significant potential for development, both in terms of natural resources and human resources. The construction of the gate aims to make Kota Guring Village have an icon that is visible and known to the outside community. Community service in building a village gate through cooperation in Kota Guring Village, Rajabasa District, South Lampung Regency aims to create a new symbol for the village that can increase the sense of togetherness and awareness of residents. The construction of the Kota Guring Village gate has several stages in building village infrastructure that will become the icon and identification mark of the village. This process is carried out with a holistic and participatory approach. The results of the construction of the gate in Kota Guring Village which was carried out on July 28, 2024 and ended on August 15, 2024. The results of this activity are not only seen in the physical form of the gate, but also have a positive impact on the community and the surrounding environment. First of all, the results of this activity can be observed through the entrance gate which stands firmly as a visual symbol of the character of the community. Therefore, the implementation of this community service activity needs to be carried out with an appropriate strategy to overcome various existing challenges and ensure the success of the construction of the village gate which will become a new icon for Kota Guring Village